2019
DOI: 10.1002/ehf2.12486
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular biomarkers predict post‐discharge re‐hospitalization risk and mortality among Swedish heart failure patients

Abstract: AimThe aim of this study was to assess the predictive role of biomarkers, associated with cardiovascular stress and its neuroendocrine response as well as renal function, in relation to mortality and risk of re‐hospitalization among consecutive patients admitted because of heart failure (HF).Methods and resultsA total of 286 patients (mean age, 75 years; 29% women) hospitalized for newly diagnosed or exacerbated HF were analysed. Associations between circulating levels of mid‐regional pro‐adrenomedullin (MR‐pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…This finding is coincident with that of other studies that report the predictive value of frailty in the general population ( 6 ) and clinical HF patients ( 21 ). The NT-proBNP level increases with the HF stage ( 22 ) and predicts mortality and readmission among patients aged ≥65 years who are hospitalized for HF ( 23 ). Our study also showed its predictive value for 1-year death or readmission in gerontal SBHF inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is coincident with that of other studies that report the predictive value of frailty in the general population ( 6 ) and clinical HF patients ( 21 ). The NT-proBNP level increases with the HF stage ( 22 ) and predicts mortality and readmission among patients aged ≥65 years who are hospitalized for HF ( 23 ). Our study also showed its predictive value for 1-year death or readmission in gerontal SBHF inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have found that copeptin exhibits early diagnosis, severity assessment and survival prognostic abilities in various patient cohorts, including acute coronary syndrome, decompensated heart failure, acute exacerbation of chronic obstructive disease, sepsis and trauma [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] In the clinical setting, specifically in HF, the natriuretic peptides (NPs) (B-type natriuretic peptide [BNP], N-terminal fraction of BNP [NT-proBNP], and midregional proANP) are markers of myocardial stress that have been widely investigated, being predictive of mortality and rehospitalization. [12][13][14] Similarly, cardiac troponins are markers of myocardial injury that have been observed to be elevated in many HF patients even in the absence of an acute coronary syndrome due to the stress and damage of myofibrillar proteins. Hence, NP and troponins concentrations may help in the diagnosis and prognosis of HF.…”
mentioning
confidence: 99%